Legal Responsibility for Livestock that Damage Other People's Crops in Village Regulations and Islamic Law - Lahmuddin Zuhri; Rabiatul Munawarah; Hanuring Ayu (International Journal of Social Science and Humanity, 2025)
The problem of livestock roaming freely in Kerato Village, Unter Iwes District, causes damage to property, agricultural land, social conflict, and economic losses. To address this problem, Kerato Village Regulation Number 7 of 2021 concerning Livestock Maintenance was created. This regulation stipulates administrative sanctions in the form of fines and compensation for livestock owners who release their livestock in public places, residential areas, and agricultural or plantation land owned by others without supervision from the livestock owner. This study uses an empirical legal research approach, a method that analyzes social phenomena in society using a legislative approach, a sociological approach, a comparative approach, and a case approach. The results of the study indicate that the legal liability of livestock owners according to Kerato Village Regulation Number 7 of 2021 concerning Livestock Maintenance stipulates that livestock owners who roam freely and damage agricultural land will be subject to administrative sanctions in the form of fines for security costs and maintenance costs for the secured livestock and are required to pay compensation for damaged crops. Research results related to Islamic law emphasize the responsibilities of livestock owners based on the principle of justice, requiring balanced compensation and encouraging dispute resolution through mediation.